Development of Nonaggregating Poly-A Tailed Immunostimulatory A/D Type CpG Oligodeoxynucleotides Applicable for Clinical Use. (25th August 2015) - Aoshi, Taiki; Haseda, Yasunari; Kobiyama, Kouji; Narita, Hirotaka; Sato, Hideaki; Nankai, Hirokazu; Mochizuki, Shinichi; Sakurai, Kazuo; Katakai, Yuko; Yasutomi, Yasuhiro; Kuroda, Etsushi; Coban, Cevayir; et al.
Abstract : Immunostimulatory CpG ODNs have been developed and utilized as TLR9-dependent innate immune activators and vaccine adjuvants. Four different types of immunostimulatory CpG ODNs (A/D, B/K, C, and P type) have been reported. A/D type ODNs are characterized by high IFN- α production but intrinsically form aggregates, hindering its good manufacturing practice grade preparation. In this study, we developed several D35-derived ODNs (a commonly used A/D type ODN), which were modified with the addition of a phosphorothioate polynucleotide tail (such as dAs40), and examined their physical properties, solubility in saline, immunostimulatory activity on human PBMCs, and vaccine adjuvant potential in monkeys. We found that two modified ODNs including D35-dAs40 and D35core-dAs40 were immunostimulatory, similar to original D35 in human PBMCs, resulting in high IFN- α secretion in a dose-dependent manner. Physical property analysis by dynamic light scattering revealed that both D35-dAs40 and D35core-dAs40 did not form aggregates in saline, which is currently impossible for the original D35. Furthermore, D35-dAs40 and D35core-dAs40 worked as better vaccine adjuvant in monkeys. These results suggested that D35-dAs40 and D35core-dAs40 are two promising prototypes of nonaggregating A/D type ODN with advantages of ease of drug preparation for clinical applications as vaccine adjuvants or IFN- α inducing immunomodifiers.